2022
DOI: 10.1007/s12144-022-03661-3
|View full text |Cite
|
Sign up to set email alerts
|

Academic stress and depression among vietnamese adolescents: a moderated mediation model of life satisfaction and resilience

Abstract: Academic stress is rising among high school students, especially in light of the Covid-19 pandemic, such as social distancing, long-term online learning, and lack of social support. Many studies have also shown that students with high levels of academic stress have a higher risk of depression. However, very few researchers are interested in studying life satisfaction as a moderate factor for the indirect relationship between academic stress and depression. This study investigated whether life satisfaction fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Specifically, positive, warm, interpersonal relationships allow children to feel more confident in facing the challenges and demands of learning by affirming themselves and generating higher core self-evaluations, thus reducing academic stress. At the same time, supportive relationships enhance children’s mental capacity and resilience for coping with academic challenges and setbacks, all of which diminish feelings of stress [ 64 , 68 ]. Conversely, negative and unsupportive interpersonal relationships reduce children’s ability to cope, which can lead to more academic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, positive, warm, interpersonal relationships allow children to feel more confident in facing the challenges and demands of learning by affirming themselves and generating higher core self-evaluations, thus reducing academic stress. At the same time, supportive relationships enhance children’s mental capacity and resilience for coping with academic challenges and setbacks, all of which diminish feelings of stress [ 64 , 68 ]. Conversely, negative and unsupportive interpersonal relationships reduce children’s ability to cope, which can lead to more academic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prolonged periods of home isolation coupled with a lack of exercise have led to increased academic pressure and belowaverage health conditions [10,12]. The results of numerous cross-sectional and longitudinal studies have confirmed that that academic stress is significantly and positively associated with depressive symptoms [3,18,[64][65][66][67].…”
Section: The Mediating Effect Of Academic Stressmentioning
confidence: 99%
“…Related studies have shown that the higher an individual’s resilience, the higher their life satisfaction, and high life satisfaction indicates good mental health and low depressive symptoms[ 32 , 33 ]. One characteristic of highly resilient individuals is that they can maintain a high level of life satisfaction in a complex environment, and the positive emotional experience generated by high life satisfaction reduces depression[ 34 , 35 ]. In view of the psychological status of nurses in the operating room, hospitals should regularly carry out psychological and physiological assessment activities for nurses in the operating room, understand the source of stimuli and the causes of nurses’ depression, and carry out targeted intervention measures to help nurses decompress psychologically, relieve fatigue and boredom, and improve their life satisfaction and psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between academic stress and psychological distress is self-evident. According to the general strain theory, stressful experiences, such as academic stress, may cause individuals involved in depression, anxiety, and other emotional problems [ 9 , 27 ]. Empirical studies demonstrated that there is a close relationship between academic stress and psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies demonstrated that there is a close relationship between academic stress and psychological distress. For example, academic stress is positively correlated with depression [ 27 ], and positively correlated with anxiety [ 28 , 29 ], academic stress significantly increases psychological stress [ 30 ], and promotes the negative mental health of adolescents, such as anxiety and depression levels [ 31 ]. Given that psychological distress is a comprehensive index reflecting the levels of depression, anxiety, and stress [ 8 ].…”
Section: Introductionmentioning
confidence: 99%